Analisis Kinerja Manajemen Keselamatan dan Kesehatan Kerja untuk Mengetahui Penyebab Meningkatnya Kecelakaan Property Damage di PT. Cakra Bumi Pertiwi Site Bengkulu Utara Provinsi Bengkulu - Renaldo Juliandi; Rijal Abdullah; Murad Murad (Journals Mining Engineering : Bina Tambang, 2018)
From the research can be seen that the incidence of property damageaccidents increased. This is caused of unsafe conditions and unsafe work acts,inconsistent in supervising the K3 management system, lack of knowledge, employeeawareness and concern about K3. The absence of sanctions against employees whoviolate K3. The purpose of this study is to reveal whether PT. CBP has implementedK3 principles in accordance with the principles of K3 mine, reveals whethersupervisors and miners have implemented K3 principles, disclosing the extent ofoccupational risk, disclosing the causes of accidents, and disclosing the percentage ofunsafe and unsafe events.In carrying out this research, combined theory and direct interview withfield data, so that both of them got problem solving approach.Based on the results of the research conducted can be concluded thefollowing points. First, the factors that cause property damage accidents includehuman factors, equipment factors and environmental factors. Second, there are stillmany unsafe and unsafe practices. Third, the percentage of accidents for unsafe actsis 60.71% and for unsafe conditions is 39.29%. And the cause of the accidentproperty damage in PT. Cakra Bumi Pertiwi is a matter of implementation of K3policy in management, which subindicator is supporting activity, capabilityguarantee, and ability guarantee.